66.9k views
3 votes
Please help lol, I have 1 question left after this one

Please help lol, I have 1 question left after this one-example-1
User Rafalotufo
by
6.3k points

1 Answer

1 vote

Answer:

see explanation

Explanation:

The n th term of an arithmetic sequence is


a_(n) = a₁ + (n - 1)d

where a₁ is the first term and d the common difference

here a₁ = 9 and d = - 2, hence


a_(n) = 9 -2(n - 1) = 9 - 2n + 2 = - 2n + 11


a_(n) = - 2n + 11 ← n th term formula

User Eriklharper
by
5.6k points